Partial Horizontal Laryngectomy and Epiglottiplasty - 皇甫辉 王斌权 孔维佳 龚树生 温树信 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
In order to evaluate the availability of the lateral horizontal laryngectomy and anaplasty of epiglottis to treat some patients with specific supraglottic carcinomas and hypopharyngeal carcinomas, 17 cases of laryngeal and hypopharyngeal carcinomas were retrospectively analyzed, whose tumors were located at the lateral margin of epiglottis, aryepiglottic fold, medial wall of piriform fossa and were treated by the lateral horizontal laryngectomy and anaplasty of epiglottis. The results showed that all cases took food by mouth in postoperative 9-14 days and subjected to decannulation in postoperative 9-15 days. Three cases had postoperative hoarse voice. The free-disease survival rate of 3 years was 71.4 % in 14 cases followed up after the first surgical therapy, and the overall free-disease survival rate of 3 years was 85.7 % after the second surgical therapy. It was concluded that the manipulations of the lateral horizontal laryngectomy and epiglottiplasty were simple. It could alleviate the postoperative symptoms of aspiration and bucking remarkably and shorten their postoperative recovery time, yet does not lower the survival rate of patients if laryngocarcinoma or hypopharyngeal carcinoma cases were properly selected.